Advanced techniques for Environmental Risk Assessment within the Oil & Gas sector - Ricciu, Marta (Alma Mater Studiorum - Università di Bologna, 2019)
Oil and gas installations in sensitive areas with harsh environmental conditions may require improved risk monitoring, assessment, and management in order to prevent and limit the damage caused by accidental hydrocarbon spills in the sea. This issue is a priority when the installation under examination is located in an area defined as sensitive. The present work deals with a real reference case study, an offshore installation located in the Barents Sea, which represents a relevant example of innovative facility operating offshore in the Arctic sensitive region. Hydrocarbon process leaks are a major contributor to offshore risk. The scenarios that may develop from the Process area of this installation have been selected through the application of a leak frequency model and the modeling of the safety barriers. The Process Leak for Offshore installation Frequency Assessment Model estimates the topside process leak frequencies for use in Quantitative Risk Analysis of fire and explosion at installations located on the Norwegian Continental Shelf. It is based on the assumption that the leak frequency is proportional to the number of each type of equipment. The performances of the safety barriers have been used as QRA parameters. The environmental risk is evaluated through an exposure-based analysis, based on duration, rate and amount of the release as well as oil drift simulation. This step has been carried out thanks to the SINTEF’s software OSCAR – Oil Spill Contingency and Response. The level of estimated risk is then compared with the stringent tolerability criteria to which installations located in sensitive areas are subjected. Further information about the impact on the ecosystem is given by the EIF factor related to different release categories.